Teaching students with intellectual disability to use English through pragmatics - Rodríguez Carreón, Yaresi Sinaí; Serrato Salazar, Dan Isaí (Red de Investigación Educativa, UANL, 2017)
The current investigation focuses on helping students with intellectual disability to use English through language pragmatics. After investigating about English as a foreign language (EFL) acquirement of these students, it was discovered that they are not acquiring the language with the methods that are commonly implemented in the regular English classrooms. By using the action-research method and by consulting appropriate literature, some specific problems of language acquirement were identified in these students. By analyzing the problems, speech acts in Role-plays were proposed as strategies to teach them in order to help them to acquire EFL. After implementing the proposal based on speech acts it could be observed that students were using English in the Role-plays, but it is still difficult for them to apply those strategies in the everyday situations.